Clinical research and care in the era of ‘N-of-1’ precision cancer medicine - Markman, Maurie (Henry Stewart Talks, 2017)
Randomized cancer clinical trials paradigm problems, Novel paradigm changes in cancer management, “Molecular matching” and “basket trials” advantages in malignant clinical trials